2017
DOI: 10.1080/10408398.2017.1344186
|View full text |Cite
|
Sign up to set email alerts
|

Grain and sweet sorghum (Sorghum bicolorL. Moench) serves as a novel source of bioactive compounds for human health

Abstract: Grain sorghum is an important staple food crop grown globally while sweet sorghum is increasingly considered as a promising biofuel feedstock. Biofuels are the major economic products from the processing of large quantities of biomass, which is currently being utilized to make value-added products in the biorefinery approach. To date, these value-added products are typically commodity chemicals and waste materials used in agriculture. However, there are opportunities to generate high-value bioactive compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 114 publications
1
32
0
Order By: Relevance
“…According to their structure, the phenolic acids can be divided into two categories: benzoic and cinnamic acid ( Figure 2). The main phenolic acids reported in sorghum grain are gallic, vanillic, protocatechuic, cinnamic, p-coumaric, p-hydroxybenzoic, syringic, ferulic, caffeic, and sinapic acids (Althwab, Carr, Weller, Dweikat, & Schlegel, 2015;Vanamala, Massey, Pinnamaneni, Reddivari, & Reardon, 2018).…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…According to their structure, the phenolic acids can be divided into two categories: benzoic and cinnamic acid ( Figure 2). The main phenolic acids reported in sorghum grain are gallic, vanillic, protocatechuic, cinnamic, p-coumaric, p-hydroxybenzoic, syringic, ferulic, caffeic, and sinapic acids (Althwab, Carr, Weller, Dweikat, & Schlegel, 2015;Vanamala, Massey, Pinnamaneni, Reddivari, & Reardon, 2018).…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Sorghum ( Sorghum bicolor (L.) Moench), the fifth primary cereal crop in the world, has been attracting much attention because of its high content of phytochemicals (Ragaee, Abdel‐Aal, & Noaman, 2006). Sorghum grains contain high portion of bioactive phytochemicals such as phenolic acids, procyanidins, 3‐deoxyanthocyanidins, and condensed tannins (Vanamala, Massey, Pinnamaneni, Reddivari, & Reardon, 2017; Xiong, Zhang, Warner, & Fang, 2019a). Epidemiological studies have consistently shown that the consumption of sorghum products is associated with reduced risk of chronic diseases, including type II diabetes, cardiovascular diseases, and cancer owing to the phenolic profile (Awika & Rooney, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the search yielded 498 articles, and 320 remained for further evaluation after 178 duplicated articles were excluded. Of the 23 full‐text reports remaining after title and abstract screening, four studies (Denova‐Gutierrez, Hernandez‐Ramirez, & Lopez‐Carrillo, ; Karagulle, Fidan, Kavgaci, & Ozdemir, ; Terry, Lagergren, Ye, Wolk, & Nyren, ; Wang et al., ) without available OR and 95% CI were ruled out, and another eight studies (Fraser, ; Gil, Ortega, & Maldonado, ; Jansen et al., ; Lafiandra, Riccardi, & Shewry, ; McCullough et al., ; Shamberger, Tytko, & Willis, ; So, Law, Law, Chan, & Chair, ; Vanamala, Massey, Pinnamaneni, Reddivari, & Reardon, ) were not included because they did not investigate cereal or grain consumption and GC risk. After this review, 11 observational studies evaluating the risk of GC remained for the analysis (Buckland et al., ; Chatenoud et al., ; Chen et al., ; De Stefani et al., ; Kasum, Jacobs, Nicodemus, & Folsom, ; Lissowska et al., ; Lucenteforte et al., ; Ramón, Serra, Cerdó, & Oromí, ; Wang et al., ; Ward, ; Zhang et al., ).…”
Section: Resultsmentioning
confidence: 99%